Analysis of Permanent Magnet Demagnetization Effect Outer-rotor Hybrid Excitation Flux Switching Motor - M. Z. Ahmad; E. Sulaiman; S.K. Rahimi; G. M. Romalan; M. Jenal (Institute of Advanced Engineering and Science, 2017)
This paper addresses the irreversible permanent magnet (PM) demagnetization analysis of hybrid excitation flux switching motor (HEFSM) with outer-rotor configuration. PM demagnetization cause the PM strength used in the motor significantly reduces and hence contributes less torque performance. The study is focused on thermal analysis and conducted at various temperature up to as high as 180 degrees Celsius which has a tendency to be demagnetized. Therefore, PM demagnetization is among a critical issue and influences the choice of the applied motor. The analysis is carried out based on finite element method (FEM) and percentage of PM demagnetization is then calculated. Finally, based on simulated and calculated results the final design outer-rotor HEFSM has only 0.85 percent PM demagnetization at very high temperature and obviously the is no PM demagnetization at normal operating conditions.